Computational Study for Band Structure Calculation of InPd Intermetallic - Bhardwaj, Purvee (Communications in Mathematics and Applications, 2025)
This paper reported the electronic and structural calculations of InPd at computational level. For studying these properties we have used Quantum Espresso code. The CsCl (B2-type) structure is where the current intermetallic crystallises. Calculations are made for the ground state parameters, including the lattice constant \((a_0)\), bulk modulus \((B)\), and its pressure derivative \((B’)\). These findings are in good agreement with those that are currently available. In order to determine thermodynamical quantities, we have also examined Murnaghan’s equation of state. Their ductility is confirmed by the current intermetallics.